Conversational Analysis: The Sociology of Talk Among Gorontalonese Speaker - Aryati Hamzah; Siti Afrianty H. Kundji (Eastasouth Institute, 2025)
This study examines everyday conversational practices among Gorontalonese speakers through the perspective of Conversation Analysis as a branch of discourse analysis. The research focuses on how social interaction is organized in natural talk, particularly in terms of turn-taking, adjacency pairs, and overlap. The data were collected through field research by recording spontaneous conversations among Gorontalo community members in various informal settings, complemented by library research to support theoretical grounding. The findings reveal that Gorontalonese conversations are characterized by flexible turn-taking mechanisms, frequent self-selection, and extensive use of cooperative overlap. Adjacency pairs such as question–answer, offer–rejection, and information–acknowledgement appear consistently, although they are often delayed or embedded within insertion sequences. In addition, back-channel signals and choral repetition are commonly used to express attentiveness, agreement, and social solidarity. These interactional features reflect the cultural norms of familiarity, closeness, and mutual engagement within the Gorontalo community. The study concludes that conversation among Gorontalonese speakers functions not only as a means of exchanging information but also as a social practice that reinforces interpersonal relationships and communal cohesion.